Translating Polysyndeton: A new approach to “Idiomaticism” - Joachim Zemmour (Angles)
This experimental study is a synthetic presentation of a series of “rules” relative to the construction of complex sentences in French, specifically with regards to the use of coordinated structures. It is an adaptation of part of my PhD dissertation, whose subject was the translation of “polysyndeton” from English into French, observed from a “pragmatic” perspective as defined by Jean-René Ladmiral. As a translatologist, my approach is neither that of a linguist, nor that of a literature scholar, but that of a researcher mainly interested in the pragmatics of translation. It is not, therefore, set within any exclusive theoretical framework, especially as far as linguistics is concerned (translatology being, by its very nature, an interdisciplinary field). The primary aim of this doctoral research was to achieve a better understanding of what is traditionally—but often too vaguely—called “idiomaticism”, more especially as regards the French language. Throughout the article, the concept of “idiomaticism” has been described as a series of “thought patterns” that have an influence on the syntax of the French sentence, without being a formal (i.e. grammatical) constituent of it. These “rules” or “tendencies” could be particularly useful for learners of French as a foreign language.